MicroRNA29B induces fetal hemoglobin via inhibition of the HBG repressor protein MYB in vitro and in humanized sickle cell mice - Gu, Qingqing; Palani, Chithra D.; Smith, Alana; Li, Biaori; Amos-Abanyie, Ernestine Kubi; Ogu, Ugochi; Lu, Lu; Pace, Betty S.; Starlard-Davenport, Athena (Frontiers in Medicine, 2022)
Sickle cell disease (SCD) is a common genetic red blood cell disorder that affects over 20 million individuals worldwide. Therapeutic strategies aimed at reactivating HBG gene transcription and fetal hemoglobin (HbF) synthesis remains the most effective strategy to ameliorate the clinical symptoms of SCD. We previously identified microRNA29B (MIR29B) as a novel HbF inducer via targeting enzymes involved in DNA methylation, namely DNA methyltransferase (DNMT) 3A and 3B. We provided further evidence that introduction of MIR29B into KU812 leukemia cells, significantly reduced MYB protein expression. In this study, in silico analysis predicted complimentary base-pairing between MIR29B and the 3’-untranslated region (UTR) of MYB. Therefore, the objective of this study was to determine the extent to which MIR29B mediates HbF induction via targeting MYB in KU812 leukemia cells and human primary erythroid progenitors. Overexpression of MIR29B significantly reduced MYB mRNA and protein expression in KU812 cells and erythroid progenitors. Using a luciferase reporter vector that contained the full length MYB 3′UTR, we observed a significant reduction in luciferase activity among KU812 cells that co-expressed MIR29B and the full length MYB 3′UTR as compared to cells that only expressed MYB 3′UTR. We confirmed the inhibitory effect of a plasmid engineered to overexpress MYB on HBG activation and HbF induction in both KU812 cells and human primary erythroid progenitors. Co-expression of MIR29B and MYB in both cell types further demonstrated the inhibitory effect of MIR29B on MYB expression, resulting in HBG reactivation by real-time PCR, Western blot, and flow cytometry analysis. Lastly, we confirmed the ability of MIR29B to reduce sickling and induce HbF by decreasing expression of MYB and DNMT3 gene expression in the humanized Townes sickle cell mouse model. This is the first study to provide evidence of the ability of MIR29B to modulate HBG transcription by DNMT3 and MYB gene silencing in vivo.